Clinical, neuroimaging and biochemical findings in patients and patient fibroblasts expressing ten novel GFM1 mutations. Issue 2 (11th November 2019) - Barcia, Giulia; Rio, Marlène; Assouline, Zahra; Zangarelli, Coralie; Gueguen, Naig; Dumas, Valerie D.; Marcorelles, Pascale; Schiff, Manuel; Slama, Abdelhamid; Barth, Magalie; Hully, Marie; de Lonlay, Pascale; et al.
Abstract: Pathogenic GFM1 variants have been linked to neurological phenotypes with or without liver involvement, but only a few cases have been reported in the literature. Here, we report clinical, biochemical, and neuroimaging findings from nine unrelated children carrying GFM1 variants, 10 of which were not previously reported. All patients presented with neurological involvement—mainly axial hypotonia and dystonia during the neonatal period—with five diagnosed with West syndrome; two children had liver involvement with cytolysis episodes or hepatic failure. While two patients died in infancy, six exhibited a stable clinical course. Brain magnetic resonance imaging showed the involvement of basal ganglia, brainstem, and periventricular white matter. Mutant EFG1 and OXPHOS proteins were decreased in patient's fibroblasts consistent with impaired mitochondrial translation. Thus, we expand the genetic spectrum of GFM1 ‐linked disease and provide detailed clinical profiles of the patients that will improve the diagnostic success for other patients carrying GFM1 mutations.